PENGARUH PENGGUNAAN D-FRUKTOSA DAN KUNING TELUR SEBAGAI PENGENCER TERHADAP KUALITAS SPERMATOZOA KAMBING PERANAKAN ETAWA (PE) DALAM PROSES SEXING DENGAN METODE SENTRIFUGASI GRADIEN DENSITAS PERCOLL PADA WAKTU BEFORE FREEZING DENGAN KECEPATAN PUTAR 2250 - Dewanttoro, Anang (Universitas Kanjuruhan Malang, 2013)
This research was conducted at the Laboratory Balai Besar Inseminasi Buatan (BBIB) Singosari Malang on 24 September until 31 October 2013. This research was to determine effect of D-fructose and eggs yolk to sperm quality of Peranakan Etawa (PE) goat in the sexing process use centrifugation gradient density percoll method on before freezing with 2250 rpm speed. The method used experiental laboratory the method of experiment by Completely Randomized Design (CRD). The material used in this research is a fresh semen Peranakan Etawa (PE) goat. Based onthe results of this research indicate that there are significant X sperm motility were significantly (P<0.05) with 2.25% D-fructose and 22.5% egg yolk and Y sperm motility also a significant effect (P<0, 01) with 1.75% D-fructose and 17.5% egg yolk having the best quality. From this study it can be concluded that the influence is evident in the use of D-fructose and eggs yolk to sperm quality of Peranakan Etawa (PE) goat in the sexing process use centrifugation gradient density percoll method on before freezing with 2250 rpm speed.Keyword : D-fructose, eggs yolk, sexing process, before freezing, Peranakan Etawa goat.